The Influence of Video Media on Motivation and Learning Outcomes of Third Grade Students in Elementary School - Anggun Radika Putri; Darmansyah Darmansyah; Alwen Bentri; Muhammadi Muhammadi (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to examine the effect of video media on students' motivation and learning outcomes in Natural and Social Sciences (IPAS) for Grade III at SD Negeri 34 Simpang Haru. Motivated by the low motivation and achievement levels among students and the limited use of interactive media, this quasi-experimental study used a Posttest-Only Control Group Design involving 52 students divided into an experimental group (video media) and a control group (PowerPoint media). Data were collected using motivation questionnaires and objective tests and analyzed using t-tests and Two-Way ANOVA. The results showed that video media significantly improved motivation (p = 0.000) and learning outcomes (p = 0.002) in the experimental group. Furthermore, there were significant differences between the two groups in both motivation (p = 0.000) and learning outcomes (p = 0.020). The Two-Way ANOVA also revealed significant interaction effects between media type and class group on motivation (F = 618.221; η² = 0.925) and learning outcomes (F = 5.809; η² = 0.104). These findings suggest that video media is an effective tool for enhancing learning, especially when aligned with classroom conditions